HTLV-I associated myelopathy in the northern region of Brazil (Belém-Pará): serological and clinical features of three cases - Ishak,Ricardo (2002)
Three patients (males, black, ages 37, 40 and 57) attended a university clinic with a progressive paraparesis of obscure origin. One patient who referred disease duration of more than 16 years, showed diminished deep reflexes, bilateral Babinski's sign, diminished sensation of vibration, abnormal bladder function and back pain. The other two patients (with one and six years of disease duration) complained of weakness in one leg, increased deep reflexes and back pain. Babinski's sign and bladder disturbance were also present in the patient with six years of disease. Blood samples tested by an enzyme immune assay and a discriminatory Western blot were positive for HTLV-I. The familial analysis of one patient showed a possible pattern of sexual and vertical transmission of the virus. To the best of our knowledge, these are the first cases of a proven association between HTLV-I and TSP/HAM in Belem, Para, and emphasize the need to actively look for cases of neurological disease associated to the virus.